The relationship between human resource management practices and organizational performance by mediating role of work motivation: A conceptual model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this study is provide a conceptual model for the relationship between HRM practices (selection, training & development programs, career development, performance management, and reward) and organizational performance by mediating role of work motivation. HRM practices are the main engine of work motivation and organizational performance, through suitable selection systems, sufficient training and development programs, fair and quick career development systems, fair performance management systems, high reward and benefits, and a high level of motivation in the work environment, which contributes to enhancing and improving organizational performance. Social exchange theory supported these relationships, where the organizational performance is impacted by HRM practices (selection, training & development programs, career development, performance management, and reward) and work motivation. This study recommended examining the proposed framework by using advanced statistical methods in order to examine the previous hypotheses and provide the results to help decision-makers in organizations.